Peking University People's Hospital : an IT-led upgrading in the new healthcare reform - McFarlan, F. Warren (Franklin Warren); Jia, Ning; Liu, Weiqu; Zhang, Hong (Economist) ([London] : SAGE, 2016)
In 2006, Dr Wang Shan was appointed as the president of Peking University People's Hospital (hereafter referred to as PKUPH), a large class 3A public hospital in China. Prior to his appointment, PKUPH had experienced three consecutive years of financial losses due to poor internal management. No standard operating procedure was established to prescribe the level of activity expected from each responsible person or decision units, and the amount of resources that a responsible party should use in achieving that level of activity. No formal management control systems were installed to collect, process, analyse accounting (particularly cost-related) information and provide timely feedback to the management. As a result, actual costs significantly exceeded budget. This case study examines this issue.
Originally Published in: McFarlan, F. W., Jia, N., Liu, W., & Zhang, H. (2013). Peking University People's Hospital: An IT-led Upgrading in the New Healthcare Reform. 5-913-311. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Peking University People's Hospital -- Management; Hospitals -- China -- Beijing -- Administration -- Case studies; Management information systems -- Case studies